The Double Ending of The Mountain and the Valley: From Aristotle to Dante - Bhojwani, Maia (Studies in Canadian Literature, 2001)
Examining the two endings of Ernest Buckler’s The Mountain and the Valley separately may shed new light on the present conviction that David’s failure to become an artist is the result of a moral flaw or the inevitable outcome of an internal deficiency. While the novel seems to have two conclusions – the false but tragic conclusion of the young man left out of the war, and the true but ironic ending of his death in the mountain – considering the double ending suggests a change in the concepts governing Buckler’s characterization of David. The themes and images in the first ending are Romantic and state a Wordsworthian belief in both the imaginative and affective stores of happy childhood and the reciprocity of man and nature. The experiences expressed in the Epilogue, or second ending, deconstruct this earlier process.